Socialising over fruits and vegetables: the biocultural importance of an open-air market in Bandar Seri Begawan, Brunei Darussalam - F. Merlin Franco; Li Ling Chaw; Nurzahidah Bakar; Siti Noraqilah Haji Abas (BMC, 2020)
Abstract Background Earth's biocultural diversity comprising biological, cultural and linguistic diversities is being eroded quickly. Our ability to recognise and appreciate what is remaining is crucial for its survival. However, not all forms of diversity are appreciated equally and a growing trend in plant blindness indicates that humans ignore plants in the environment. In this context, open-air markets emerge as cultural spaces that bring people closer to each other, as well as with local biodiversity represented by fruits, vegetables and medicinal plants. Methods We conducted a cross-sectional survey with 160 people visiting Tamu Kianggeh of Bandar Seri Begawan, Brunei Darussalam. We randomly interviewed every fifth adult visitor (> 18 years) leaving the market on Fridays and Sundays continuously for a month, using a structured questionnaire. The questionnaire had 18 questions related to demographic particulars, reasons for visiting the market, vendor preference, social networking and visits to open-air markets and supermarkets. Results and discussion People visit the market for the diversity of vegetables/fruits; local fruits and vegetables; socialising; cheap prices; ability to bargain; freshness of the products; convenience; medicinal plants; snacks; leisure etc. The ethnic diversity represented at the market comprised chiefly of Malay, Kedayan, Iban, Dusun, Tutong, Chinese communities and foreigners. Majority of the respondents chose 'availability of a wide range of fruits and vegetables' as the primary reason for the visit, followed by 'availability of local fruits and vegetables'. Tamu Kianggeh sold larger number of fruits and vegetables (104 taxa, 26 natives, 2 endemics) compared to the nearest supermarket (85 taxa, 14 natives and 1 endemic). A significant number of respondents also reported that they had made friends at the market. Conclusion Tamu Kianggeh is a meeting ground for ethnic and biological diversities, a property that makes them important centres of biocultural diversity at the local level. Open-air markets such as Tamu Kianggeh bring people closer to a diverse range of vegetables and fruits. They also bring people closer to each other by serving as platforms for socialising. We propose that strategies developed to counter plant blindness should also consider the potential of open-air markets.